Efficacy and Controversies Surrounding Electroconvulsive Therapy for Treatment-Resistant Depression: A Literature Review - Czupryńska, Karolina; Otręba, Karina; Daniel, Piotr; Leśkiewicz, Michał; Składanek, Justyna; Cieszkowska, Joanna (Journal of Education, Health and Sport, 2024)
Electroconvulsive therapy (ECT) remains a vital treatment option for individuals with treatment-resistant depression (TRD). Despite its historical stigma, controversy, and limited accessibility, ECT has been demonstrated to be beneficial and effective in severe cases of depressive disorders, where medication fails to produce results. It has been utilized since 1938 as a therapeutic technique for various psychiatric disorders, often used as an alternative to chemically induced seizures. The public’s perspectives on ECT hold significance as they can shape attitudes toward patients undergoing this therapy and the discrimination associated with receiving ECT. Additionally, the perspectives of patients who may benefit from ECT and those who are already undergoing treatment are crucial as they can influence treatment decisions and consent processes. This literature review examines the efficacy and controversies surrounding ECT in the management of TRD. Studies assessing the effectiveness of ECT in TRD, along with associated adverse effects and ethical considerations, are reviewed. Additionally, the role of ECT in contemporary psychiatric practice and its comparison with alternative treatments for TRD are discussed. The review highlights the complex interplay between clinical efficacy, safety, patient preferences, and societal perceptions in shaping the utilization of ECT in the treatment of TRD.